Application of cloud computing in the Hungarian SME sector - Nagy-Borsy, Viktor (Studia Mundi – Economica, 2020)
The diffusion of infocommunication technologies in the society and the economy and the effects of digitalisation are seem to indicate a shift towards a service-oriented economy. The cloud computing services fit into this trend, and, with a little exaggeration, these solutions are easy to use and available to everyone. The benefits of using cloud-based technologies are particularly well-suited to the characteristics and specialties of small and medium-sized enterprises. The aim of the study is to examine the tendencies in relation to the use and spread of cloud computing services in the Hungarian SME sector, in the European Union context.